Analyzing Implementation of 2013 Curriculum for Elementary School in Indonesia - Fu’addiyah, Tsamrotul; Alpusari, Mahmud; Hermita, Neni (Proceedings of the UR International Conference on Educational Sciences, 2018)
Education can be obtained through school, in each school the implementation in learning uses guidelines which are in the form of a curriculum. Learning of the curriculum of 2013 is learning that links core competenciesâ and indicator that are put together from several subjects. Observation results found that the implementation of the curriculum 2013 learning still appear difficult in correlating subjects with themes. Purpose of the research to describe the implementation of the 2013 curriculum at elementary school. The research method used is descriptive research method. The subjects of this study were all students of grade elementary school 03 Langsat Permai that consists of 23 students. Data collection techniques that has been collected soberly without any intention to make generalizations from results of the research. The results of the study in the implementation of the 2013 curriculum learning in grade 5 in public elementary school of 03 Langsat Permai were in accordance with the learning tools made by the teacher and students learning activities were good such as observing, reading, writing, practicing and trying.